1989
DOI: 10.1016/0014-5793(89)80687-8
|View full text |Cite
|
Sign up to set email alerts
|

Sheep brain glutathione reductase: Purification and general properties

Abstract: Sheep brain glutathione reductase was purified about 11000‐fold with an overall yield of 40%. The method included ammonium sulphate fractionation, heat denaturation, 2′,5′‐ADP Sepharose 4B and Sephadex G‐200 chromatography steps. Specific activity at the final step was 193 IU/mg. The M r of the enzyme was found to be 116000 by gel filtration chromatography. On SDS‐PAGE, two identical subunits of M r 64000 were obtained. From the spectral data, about 2 mol FAD per mol of enzyme were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Hence, these pH values are accepted as optimal pH values. Research showed that these results are highly parallel to other results in the literature 8,37,[42][43][44] . For optimal temperature calculation of the enzymes, activities of optimal ionic strength and optimal pH enzymes were measured at 10 C intervals within 10-70 C range.…”
Section: Discussionsupporting
confidence: 82%
“…Hence, these pH values are accepted as optimal pH values. Research showed that these results are highly parallel to other results in the literature 8,37,[42][43][44] . For optimal temperature calculation of the enzymes, activities of optimal ionic strength and optimal pH enzymes were measured at 10 C intervals within 10-70 C range.…”
Section: Discussionsupporting
confidence: 82%
“…Little is known about the biochemical properties and the localization of GR in brain. So far the purification of GR has been reported for sheep brain (Acan and Tezcan, 1989). The kinetic parameters of the purified GR (Acan and Tezcan, 1991) and the inhibition of the enzyme by Cd 2+ (Acan and Tezcan, 1995) have been published.…”
mentioning
confidence: 99%
“…The isoenzymes were eluted with a gradient of 0-0.5 mM GSH and 0-1 mM NADPH in 50 mM Kphosphate, containing 1 mM EDTA (pH 7.3). Active fractions were collected and dialyzed with equilibration buffer at 4 C (Acan & Tezcan, 1989;Boggaram et al, 1979;Carlberg & Mannervik, 1981).…”
Section: Preparation Of the Hemolysatementioning
confidence: 99%